Formulation and Evaluation of Physical Characteristics of Red Rice Extract (Oryza Glaberrima Steud) Lotion - Rety Setyawaty; Widayat Widayat; Dewanto Dewanto (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Red rice (Oryza Glaberrima Steud) is source of carbohydrates. The components of red rice (Oryza Glaberrima Steud) are vitamin E, thiamin, magnesium, vitamin B6, minerals and fiber. Red rice, besides having many nutrients, is also beneficial for skin care. The purpose of this study was to make lotion preparations from thick red rice extract (Oryza Glaberrima Steud) by maceration method.The method used is maceration. The yield of thick red rice extract is 5%. Variations used were variations in stearic acid, 1.5%, 3% and 4.5% and triethanolamine, 0.5%, 0.75% and 1.5%. Other ingredients used as lotion makers are 1% glycerin, 0.1% methyl paraben and as much volume as aquadest lotion. The volume of lotion made is 50 ml. The test of lotions is organoleptic, homogeneity, pH, irritation, dispersion, adhesion and type of emulsion.The results showed that the lotion smelled distinctive, had a bitter taste and was creamy/ brownish white. Lotion has a pH of 6, dispersion and adhesion according to the requirements, homogeneous lotion, preparations made do not show any irritation, and are all types of emulsion o/w. Based on the results of the study it can be concluded that brown rice can be used as a raw material for lotions.